Prophylactic Effect of Lactobacillus fermentum TKSN02 on Gastric Injury Induced by Hydrochloric Acid/Ethanol in Mice Through Its Antioxidant Capacity - Hu, Tiantian; Zhou, Liang; Wang, Xiaoli; Zhou, Xianrong; Yi, Ruokun; Long, Xingyao; Zhao, Xin (Frontiers in Nutrition, 2022)
In this article, the preventive and protective effect of a new Lactobacillus fermentum, (Lactobacillus fermentum TKSN02: LF-N2), which was isolated and identified from Xinjiang naturally fermented yogurt, on hydrochloric acid (HCl)/ethanol induced gastric injury in mice was studied. A total of 40 mice were divided into the following five groups: normal, model, LF-N2, LB (Lactobacillus bulgaricus), and Ranitidine groups. Except for the normal and model groups, mice in the other groups were treated with LF-N2, LB (Lactobacillus bulgaricus), and Ranitidine separately, and the injury of the gastric tissue was observed by taking photos and pathological sections. The levels of oxidation indicators, gastrointestinal hormone and the inflammatory cytokines in serum and gastric tissue in each group were measured. Further more, the gene expression levels of oxidative stress and inflammation related genes in the colon tissue were determined by the Real-Time PCR method. Pathological observation confirmed that LF-N2 could inhibit the gastric injury caused by HCl/ethanol. Observation of the appearance of the gastric indicated that LF-N2 could effectively reduce the area of gastric injury. Biochemical results showed that the serum gastrin (GAS) and gastric motilin (MTL) levels in the LF-N2 group were significantly lower and the serum somatostatin (SS) level was higher than in the model group and there was no significant difference between all treatment groups. The activities of total superoxide dismutase (T-SOD) and glutathione (GSH) were increased while the malondialdehyde (MDA) content was decreased in LF-N2 treatment group mice, which suggested that LF-N2 has a good antioxidant effect. Further RT-PCR experiments also showed that LF-N2 could promote the related mRNA expression of antioxidant enzymes (Cu/Zn-SOD, Mn-SOD, and CAT) and anti-inflammatory cytokines (IL-4, and IL-10), while it inhibited the gene expression of pro-inflammatory cytokine (IL-6) and apoptosis factor (Caspase-3). As observed, LF-N2 exerted a good preventive effect on HCl/ethanol induced gastric injury in mice, and the effect was close to that of LB, which indicated that LF-N2 has potential use as a probiotic due to its gastric injury treatment effects.